Regional elections in Portugal the Azores and Madeira: Persistence of non-alternation and absence of non-statewide parties. Issue 3 (27th May 2019) - Ruel, Teresa
ABSTRACT: The ruling parties were elected into office again after the recent regional elections held in Madeira (29 March 2015) and in Azores (16 October 2016): the social-democrats (PSD – Partido Social Democrata ) in Madeira and the socialists (PS – Partido Socialista ) in Azores. Despite forty years of regional elections in Portugal a pattern of non-alternation in executive government (Madeira) and the same party being in office for a long time (Azores) still has not been broken. The most notable difference is that turnout registered the lowest scores since the first regional elections were held in the 1970s. Just a bit more than 50% of voters showed up at the ballot box.